Effect of foliar spray of bioregulators and irrigation on dry matter accumulation of mustard (Brassica juncea L.) (Bangladesh Journal of Agricultural Research, 2020)
Abstract Not AvailableBangladesh J. Agril. Res. 44(4): 689-693, December 2019